Diethyl 4,4′-(3,6-dioxaoctane-1,8-diyldioxy)dibenzoate - Ma, Zhen (International Union of Crystallography, 2012)
The title compound, C(24)H(30)O(8), was obtained by reaction of ethyl 4-hydroxybenzoate with 1,2-dichloroethane. The molecule occupies a crystallographic inversion center, with its central ethylene bridge in an anti conformation. The other ethylene bridge has a gauche conformation, with the corresponding O—C—C—O torsion angle being 74.2 (1)°. The benzene rings are almost coplanar with the adjacent ethoxycarbonyl groups, with an r.m.s. deviation of 0.078 Å.